Glicosilação regiosseletiva da hesperetina catalisada por Cunninghamella echinulata ATCC 9244, em biorreator - Carvalho, Pedro Henrique de Oliveira (2019)
Introduction: Hesperetina is a flavonoid, belongs to flavanones class, with several pharmacological activities, the most cited being the antioxidant potential. However, it presents low solubility and consequently low bioavailability, making it difficult to apply it in a systemic pharmaceutical formulation. Glycosylation of hesperetin effectively modifies its pharmacokinetic properties, increasing its antidiabetic, antitilipidemic activity and efficacy against helicobacter pylori. Filamentous fungi are used in biotechnological processes to increase the activity of molecules, being able to glycosylate, regio and stereoselective derivatives, with less cytotoxicity. Cunninghamella belongs to the class of filamentous fungi capable of catalyzing glycosylation reactions. With the demand of scale-up the production of bioactive compounds, bioreactors are a promising strategy, providing a controlled environment. Aim: The objective of this work was to scale-up the regioselective glycosylation of hesperetin catalyzed by Cunninghamella echinulata 9244 in a bioreactor, with pharmacological activities improved. Methods: Hesperetin was incubated with the microorganism in PDSM medium on two scales, semi-preparative (100 mL) and preparative (2 L). HPLC-MS was used to monitoring and the caracterization of the product formed was confirmed by 1H13C NMR. Tests of anticancer and cytotoxicity were realized. Results and Discussion: The glycosylation yield in the semi-preparative scale was 0.8%, while in the preparative scale the result was 22.9%. The increase in yield can be explained by the automated control of the main parameters such as pH and oxygenation. The ideal time for biosynthesis of the glycosylated derivative in bioreactor was 72 hours. The purified product glycosylated was identified by NMR in hesperetin 7-O-β-D-glucopyranoside, not exhibiting anticancer activity, but with reduction of cytotoxicity, with IC 50 9.5 times lower than the starting compound. Conclusions: Regioselective glycosylation of hespertin was performed in a single step in bioreactor, significantly increasing the yield. The chromatographic procedure proposed by the HPLC-MS allowed a fast and efficient identification and characterization of the derivative.